2017
DOI: 10.1016/j.electacta.2017.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemistry of alternating ambipolar copolymers of 4,4′- and 2,2′-bipyridine isomers and quaterthiophene

Abstract: of alternating ambipolar copolymers of 4,4 -and 2,2 -bipyridine isomers and quaterthiophene, Electrochimica Acta http://dx.doi.org/10. 1016/j.electacta.2017.01.076 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 86 publications
(108 reference statements)
2
10
0
Order By: Relevance
“…Compounds 2, 8, 9, 19, 22, and 24 were expected to be good candidates for surface patterning, keeping in mind that 4,4′-bipys are often used as connectors in 1D/2D/3D self-assembled molecular architectures. To confirm the ability of 2,2′ and 2,2′,6,6′ or 3,3′ functionalized 4,4′-bipys to physisorb and organize on surfaces into ordered supramolecular structures, scanning tunneling STM experiments revealed that 2,2′-substituted 4,4′-bipys (2, 8, 9) are more prone to self-assemble into ordered patterns than 3,3′-substituted bipys (19,22,24). As shown in Figure 3, compounds 2, 8, and 9 formed highly ordered 2D supramolecular assemblies stabilized via van der Waals interactions between the molecules and the underlying HOPG surface.…”
Section: ■ Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…Compounds 2, 8, 9, 19, 22, and 24 were expected to be good candidates for surface patterning, keeping in mind that 4,4′-bipys are often used as connectors in 1D/2D/3D self-assembled molecular architectures. To confirm the ability of 2,2′ and 2,2′,6,6′ or 3,3′ functionalized 4,4′-bipys to physisorb and organize on surfaces into ordered supramolecular structures, scanning tunneling STM experiments revealed that 2,2′-substituted 4,4′-bipys (2, 8, 9) are more prone to self-assemble into ordered patterns than 3,3′-substituted bipys (19,22,24). As shown in Figure 3, compounds 2, 8, and 9 formed highly ordered 2D supramolecular assemblies stabilized via van der Waals interactions between the molecules and the underlying HOPG surface.…”
Section: ■ Introductionsupporting
confidence: 90%
“…The nucleophilic addition of a Grignard reagent with a long alkyl chain (ClMgC 18 H 37 ) also failed, and these methods were not pursued any further. In a less direct synthesis inspired by work of Fürstner et al., a Kumada coupling reaction of 2,2′-dichloro-4,4′-bipyridine ( 1 ) with ClMgC 18 H 37 in the presence of 10 mol % Fe­(acac) 3 gave the dialkyl product 2 in 34% yield (Scheme ). In addition, 4,4′-bipy, resulting from dehalogenation, was recovered in 10% yield from a mixture containing other side products.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations